Editorial - Sierra, Javier (Street Art & Urban Creativity, 2024)
Historically, the relationship between cinema and the city has served as a mirror to reflect and shape the understanding of urban spaces and their evolution. The city not only acts as a backdrop for cinematic narratives but often becomes a central character, rich in meaning and symbolism. This call for papers seeks to delve into how cinema, as an artistic and cultural medium, represents, interprets, and transforms the vision of cities and their communities. Cinema has the power to influence our perception of the urban environment, highlighting aspects of urban life ranging from architecture and urban design to social and cultural phenomena. Through its lens, we can explore themes such as gentrification, urban identity, collective memory, and the interaction between the individual and public space. The cinematic representation of the city not only reflects existing realities but can also anticipate future urban and social transformations. We are looking for papers that explore the synergy between cinema and the city from multiple angles and disciplines. We are interested in analyses that address how cinema uses the city as a canvas for storytelling, how it captures and contributes to urban aesthetics, and how it can be a tool for social commentary and critique. Articles may examine both historical and contemporary representations of the city in cinema, as well as futuristic and speculative projections. This call is open to approaches ranging from specific case studies to theoretical and comparative analyses. We encourage researchers, academics, filmmakers, and professionals from related fields to submit papers that not only deepen the understanding of cinema and the city but also explore the possible interactions between these two vital elements of human expression and experience.